(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2023)
The objective of this study was to evaluate and demonstrate the production performance of “Koekoek Potchefstroom” chickens in pastoral areas of Hammer woreda. Twenty women pastorals from rural areas were purposely selected based on their interest to construct chicken shelters or who had house access, interest to rear exotic chickens, well-managing ability and up-come all related challenges, enough time for chickens, cover the required inputs costs and ability to recording production data. Training on poultry housing construction, poultry health, feeds and feeding, watering and important data recording system were given. Quantitative data like body weight, egg weight and first egg laying date were taken. Data were analyzed using SPSS software (v-21). Results revealed that the mortality of chicks from 45 to 60 days was 5%. The overall mortality from 60 days to 90 days was 8.75%. About 83.5% of the chicken survived until the laying age. The overall mean body weights were 0.96, 1.91, 2.14 and 2.12 kg at 3, 5, 7 and 9th month’s age, respectively. Body weight at different ages was significantly different between the sexes. The average weight of eggs at 24, 28, 34 and 38 weeks of age were 47.3±0.9, 47.3±1.1, and 48.2±0.9 and 46.9±1.3 g, respectively. Age at first egg laying was recorded as 167.4 days. The major causes of death were diseases (Coccidiosis) and poor management practices like lack of follow-up, letting them go out of their home and allowing them to scavenge and poor nutrition. In a conclusion, this breed has been familiarized with scavenging and partial-scavenging production areas of the existing pastoral system with appropriate housing, feeding and good health service provision. Verification in large-scale pastoral areas with different breeds should also be seen to look at its full potential as compared to agrarian areas. Int. J. Agril. Res. Innov. Tech. 12(2): 1-6, December 2022